Difference between Learning Basic Form Generation and Automotive Exterior Design - Shih-Hung Cheng; Yung-Chuan Ma; Winger Sei-Wo Tseng (MDPI AG, 2019)
This study explores the correlation between learning about basic form factors and learning automotive exterior design (AED) for the first time. To help beginner AED students learn smoothly, we developed modular courses and proposed to teach basic form generation. Six modular assignments were developed for the courses on Form Theory and Transportation Design, and 22 and 20 students, respectively, completed all the assignments of each course. All students were guided to become familiar with the five form factors: proportion, contour, volume, surface, and detail. According to the student self-assessments and responses for the Form Theory course, students gained a statistically equivalent learning experience of form factors from the four assignments; however, they gained significantly different levels of understanding and confidence. There was also a significant difference in understanding form factors during AED clay modeling. Further, students considered that the last two assignments in the Form Theory course had a significantly stronger relationship with learning AED than the first two assignments did. These findings are conducive to ensuring improvements in the modular courses to help future students begin learning AED.